2022
DOI: 10.3390/bioengineering9090455
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Oronasal Fistula with Tongue Flap: A Cleft Palate Report

Abstract: Oronasal fistula can persist after conventional secondary alveolar bone graft surgery, which may lead to functional issues, such as regurgitation of fluids from the oral to the nasal cavity. This manuscript describes a clinical case of a patient with a bilateral cleft lip and palate that underwent tongue graft surgery for closure of an oronasal fistula after three failed local mucosa flap surgeries. The multidisciplinary treatment was comprised of orthodontic treatment, mucosa and alveolar grafts for palate cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…In the current study, only two midline cleft type cases were observed and both cases showed bilateral agenesis of maxillary central and lateral incisors within the cleft. Our findings are in agreement with the previous studies.. 25 , 26 ) To our knowledge, very little information on the pattern of missing teeth in midline cleft type is present until now. 15 Moreover, maxillary central incisors are missing inside the cleft in CLPR, CLPL, CLPB and CLPM.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, only two midline cleft type cases were observed and both cases showed bilateral agenesis of maxillary central and lateral incisors within the cleft. Our findings are in agreement with the previous studies.. 25 , 26 ) To our knowledge, very little information on the pattern of missing teeth in midline cleft type is present until now. 15 Moreover, maxillary central incisors are missing inside the cleft in CLPR, CLPL, CLPB and CLPM.…”
Section: Discussionsupporting
confidence: 93%